Legal Politics in the Draft Criminal Procedure Code (KUHAP) in Indonesia - Hudha Bagus Setyadi; Ali Masyhar (Journal of Literature Review, 2025)
This article examines the legal politics embedded in the draft of the Indonesian Criminal Procedure Code (KUHAP). The current KUHAP, enacted in 1981, is considered inadequate in addressing the challenges posed by technological advancements, changes in the constitutional system, and increasingly complex social and legal dynamics. The new KUHAP draft aims to provide clearer legal certainty, strengthen human rights protection, and align with international conventions ratified by Indonesia. Through literature review and document analysis, this study reveals that the KUHAP draft represents a manifestation of legal politics striving to balance effective law enforcement with human rights protection. The draft emphasizes the principles of legality and presumption of innocence, introduces stricter supervisory mechanisms, and offers special protection for vulnerable groups alongside recognition of electronic evidence. Despite significant progress, the draft faces challenges such as potential abuse of authority, inter-agency conflicts, and resource readiness. Recommendations include harmonizing authorities, strengthening supervision, enhancing human resource capacity, and encouraging public participation in evaluation and refinement. This article contributes significantly to understanding the legal politics shaping criminal procedure reform in Indonesia.